Plate Tectonics Continental Drift and Mountain Building - Frisch, Wolfgang; Meschede, Martin; Blakey, Ronald C. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This textbook explains how mountains are formed and why there are old and young mountains. It provides a reconstruction of the Earths paleogeography and shows why the shapes of South America and Africa fit so well together. Furthermore, it explains why the Pacific is surrounded by a ring of volcanos and earthquake-prone areas while the edges of the Atlantic are relatively peaceful. This thoroughly revised textbook edition addresses all these questions and more through the presentation and explanation of the geodynamic processes upon which the theory of continental drift is based and which have led to the concept of plate tectonics. It is a source of information for students of geology, geophysics, geography, geosciences in general, general natural sciences, as well as professionals, and interested layman.
1. Contractional theory, continental drift and plate tectonics -- 2 Plate movements and their geometric relationships -- 3. Continental graben structures -- 4. Passive continental margins and abyssal plains -- 5. Mid-ocean ridges -- 6. Hot spots -- 7. Subduction zones, island arcs and active continental margins -- 8. Transform faults -- 9. Terranes -- 10. Early Precambrian plate tectonics -- 11. Plate tectonics and mountain building -- 12. Old orogens -- 13. Young orogens - the Earth's loftiest places.
Keywords: Geology; Geodynamics; Geomorphology; Geology; Geodynamics; Geomorphology